The Epidemiological Pattern and Co-infection of Influenza A and B by Surveillance Network From 2009 to 2014 in Anhui Province, China - He, Jun; Hou, Sai; Chen, Yue; Yu, Jun-Ling; Chen, Qing-Qing; He, Lan; Liu, Jiang; Gong, Lei; Huang, Xin-Er; Wu, Jia-Bing; Pan, Hai-Feng; Gao, Rong-Bao (Frontiers in Public Health, 2022)
Influenza-like illness (ILI) is one of the most important public health problems globally, causing an enormous disease burden. Influenza infections are the most common cause of ILI. Therefore, information on the epidemiological patterns of influenza A and B can help us to implement different strategies for selecting vaccine formulations and monitoring potential recombinant viruses. Here, we analyzed the surveillance data of 5 years from 2009 to 2014 collected by the Chinese National influenzas network in Anhui province, China. The results showed that the weekly ratio of ILI was 3.96% ± 1.9% (95% CI 3.73%-4.2%) in outpatients. The highest affected population was children under 5 years old. The epidemic of influenza viruses was highest during 2009-2010. For the other 4 surveillance years, school-aged people (5-14 years) were the most highly affected population. Influenza B and H3N2 viruses were more prevalent than H1N1pdm09 virus after 2010. In addition, a significant co-circulation of influenza A (H1N1pdm09 and H3N2) and influenza B virus was detected with 0.057% PCR positive rate during 2009-2014 in Eastern China, yet isolated only in pediatric patients. Our data reveals that school-aged population would be the main population for influenza control, and shows a distinct seasonality in Anhui Province, China. Ongoing surveillance is critical to understand the seasonality variation and make evidence-based vaccination recommendations.